Earthquake Engineering for Nuclear Facilities - Hamada, Masanori; Kuno, Michiya; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book is a comprehensive compilation of earthquake- and tsunami-related technologies and knowledge for the design and construction of nuclear facilities. As such, it covers a wide range of fields including civil engineering, architecture, geotechnical engineering, mechanical engineering, and nuclear engineering, for the development of new technologies providing greater resistance against earthquakes and tsunamis. It is crucial both for students of nuclear energy courses and for young engineers in nuclear power generation industries to understand the basics and principles of earthquake- and tsunami-resistant design of nuclear facilities. In Part I, "Seismic Design of Nuclear Power Plants", the design of nuclear power plants to withstand earthquakes and tsunamis is explained, focusing on buildings, equipment's, and civil engineering structures. In Part II, "Basics of Earthquake Engineering", fundamental knowledge of earthquakes and tsunamis as well as the dynamic response of structures and foundation ground are explained.
Introduction to Earthquake-Resistant Design of Nuclear Power Plants -- Assessment of Standard Seismic Motion -- Stability Assessment of Foundation Ground and Surrounding Slope -- Earthquake-Resistant Design of Building and Structure -- Earthquake-Resistant Design of Equipment and Piping -- Earthquake-Resistant Design of Important Civil Engineering Structures -- Tsunami-Resistant Design -- Seismic Probabilistic Risk Assessment -- International Standards and National Regulation on Seismic Safety Assessment -- Planning, Construction, Operation, and Decommission of Nuclear Power Plants -- Radioactive Waste Treatment and Disposal Technique -- Future Technology for the Seismic Safety of Nuclear Power Facilities -- Earthquake, Ground Motion, and Tsunamis -- Dynamic Response Analysis -- Earthquake-Resistant Design.
Keywords: Nuclear engineering; Buildings -- Design and construction; Natural disasters; Nuclear Energy; Building Construction and Design; Natural Hazards